2016
DOI: 10.1002/hed.24484
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiotherapy versus concurrent chemoradiotherapy for the management of high‐risk salivary gland carcinomas

Abstract: Until prospective evidence is available, such as from Radiation Therapy Oncology Group 1008, the standard use of CRT for advanced salivary malignancies cannot be recommended. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1708-1716, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 38 publications
1
65
0
Order By: Relevance
“…Despite the small subject numbers in each treatment arm, our data suggest that the presence of ENE in patients with SGC may not justify aggressive treatment intensification as HNSCC. In the literature, several retrospective series have demonstrated that adding concomitant chemotherapy to adjuvant irradiation is not associated with survival advantages . Among older patients, the use of chemoradiation is even associated with increased mortality .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the small subject numbers in each treatment arm, our data suggest that the presence of ENE in patients with SGC may not justify aggressive treatment intensification as HNSCC. In the literature, several retrospective series have demonstrated that adding concomitant chemotherapy to adjuvant irradiation is not associated with survival advantages . Among older patients, the use of chemoradiation is even associated with increased mortality .…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is mainly restricted to locally recurrent or distant metastatic disease, although CRT may not improve survival . Still, contradictory results have been reported .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from small, single‐institution studies, there is a lack of evidence in the literature for the use of adjuvant chemotherapy in salivary gland tumors beyond its use for inoperable or metastatic disease. Recent studies have suggested increased toxicity and no survival benefit associated with the addition of chemotherapy to the standard adjuvant therapy of postoperative radiotherapy of salivary gland malignancies . A Radiation Therapy Oncology Group clinical trial aiming to address the efficacy of adjuvant chemoradiotherapy is ongoing and has an estimated completion date of October 2023 (NCT01220583).…”
Section: Introductionmentioning
confidence: 99%